Geomagnetically conjugate observations of ionospheric and thermospheric variations accompanied by a midnight brightness wave at low latitudes 2. Aeronomy - Fukushima D. (2017)
© 2017 The Author(s). We conducted geomagnetically conjugate observations of 630-nm airglow for a midnight brightness wave (MBW) at Kototabang, Indonesia [geomagnetic latitude (MLAT): 10.0°S], and Chiang Mai, Thailand (MLAT: 8.9°N), which are geomagnetically conjugate points at low latitudes. An airglow enhancement that was considered to be an MBW was observed in OI (630-nm) airglow images at Kototabang around local midnight from 2240 to 2430 LT on February 7, 2011. This MBW propagated south-southwestward, which is geomagnetically poleward, at a velocity of 290 m/s. However, a similar wave was not observed in the 630-nm airglow images at Chiang Mai. This is the first evidence of an MBW that does not have geomagnetic conjugacy, which also implies generation of MBW only in one side of the hemisphere from the equator. We simultaneously observed thermospheric neutral winds observed by a co-located Fabry-Perot interferometer at Kototabang. The observed meridional winds turned from northward (geomagnetically equatorward) to southward (geomagnetically poleward) just before the wave was observed. This indicates that the observed MBW was generated by the poleward winds which push ionospheric plasma down along geomagnetic field lines, thereby increasing the 630-nm airglow intensity. The bottomside ionospheric heights observed by ionosondes rapidly decreased at Kototabang and slightly increased at Chiang Mai. We suggest that the polarization electric field inside the observed MBW is projected to the northern hemisphere, causing the small height increase observed at Chiang Mai. This implies that electromagnetic coupling between hemispheres can occur even though the original disturbance is caused purely by the neutral wind.[Figure not available: see fulltext.]